The effect of formal, neonatal communication-intervention training on mothers in kangaroo care - Alta Kritzinger; Elise van Rooyen (AOSIS, 2014)
Background: Due to low-birth-weight, preterm birth, HIV and/or AIDS and poverty-related factors, South Africa presents with an increased prevalence of infants at risk of language delay. A Kangaroo Mother Care (KMC) unit offers unique opportunities for training. Aim: The aim of the present study was to determine if formal, neonatal communication-intervention training had an effect on mothers' knowledge and communication interaction with their high-risk infants. Methods: Three groups of mothers participated: Group 1 was trained whilst practicing KMC; Group 2 was not trained but practiced KMC; and Group 3 was also not trained but practiced sporadic KMC. Ten mothers per group were matched for age, education level and birth order of their infants. The individual training was based on graded sensory stimulation and responsive mother-infant communication interaction, which emphasised talking and singing by the mother. Results: Significant differences were found in mother-infant communication interaction between all three groups, which indicated a positive effect on Group 1 with training. Group 2, KMC without training, also had a positive effect on interaction. However, Group 1 mothers with training demonstrated better knowledge of their infants and were more responsive during interaction than the other two groups. Conclusion: The present study suggests that neonatal communication-intervention training adds value to a KMC programme.